2018
DOI: 10.1037/hea0000633
|View full text |Cite
|
Sign up to set email alerts
|

Anhedonia and smoking cessation among Spanish-speaking Mexican-Americans.

Abstract: Contrary to prior research, the results of this study did not confirm the unique predictive role of low positive affect/anhedonia among Mexican Americans, suggesting that risk factors for this group may be different from other populations and cessation approaches may also need to differ. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…The absence of significant associations of positive affect with smoking and at-risk drinking in the present study is consistent with mixed findings from prior research that investigated associations of positive affect with smoking and at-risk drinking among Latinos (Cano et al, 2017; Haslam et al, 2018; Karriker-Jaffe et al, 2016). Positive affect’s association with lower odds of insufficient fruit and vegetable consumption and insufficient physical activity aligns with prior findings among non-Latino samples (Conner et al, 2015; Kiviniemi & Duangdao, 2009; Schultchen et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The absence of significant associations of positive affect with smoking and at-risk drinking in the present study is consistent with mixed findings from prior research that investigated associations of positive affect with smoking and at-risk drinking among Latinos (Cano et al, 2017; Haslam et al, 2018; Karriker-Jaffe et al, 2016). Positive affect’s association with lower odds of insufficient fruit and vegetable consumption and insufficient physical activity aligns with prior findings among non-Latino samples (Conner et al, 2015; Kiviniemi & Duangdao, 2009; Schultchen et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, positive affect also was found to be indirectly associated with smoking cessation through its relationship with self-efficacy (Castro et al, 2014). Haslam et al (2018) found that anhedonia (i.e., low positive affect) was associated with failed smoking cessation when controlling for the effects of sociodemographic characteristics and heaviness of smoking; however, the relationship was not statistically significant when controlling for other symptoms of depression. Regarding atrisk drinking, one study of Latino emerging adults found that anhedonia was positively associated with alcohol use severity (Cano et al, 2017).…”
Section: Affect and Health Risk Behaviors Among Latinosmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, transdiagnostic models of psychopathology and addictive behavior posit basic psychological mechanisms underpin such patterns of comorbidity (Kim & Hodgins, 2018; Leventhal & Zvolensky, 2015). Findings in the present study are in line with this perspective and therefore, assessment and intervention programming for anxiety–smoking comorbidity among Latinx smokers could usefully be focused on anxiety sensitivity and presumably, other basic psychological mechanisms (e.g., anhedonia; Haslam et al, 2018; Zvolensky et al, 2021; emotion dysregulation; Zvolensky, Shepherd, et al, 2019) linked to smoking among this population. There have been integrated approaches for smoking cessation that specifically engage anxiety sensitivity in efforts to decrease interoceptive perturbation, increase smoking cessation success, and improve mental health (Smits et al, 2021; Zvolensky et al, 2014; Zvolensky, Garey, et al, 2019).…”
Section: Discussionsupporting
confidence: 84%
“…Paul Cinciripini and David Wetter, conducted at the University of Texas MD Anderson Cancer Center. Details of the design, recruitment, and inclusion/exclusion criteria for each of the studies have been described in detail elsewhere and include: Breakfree 49 , CARE 50 , CASSI 51 , MIND 52 , PNS 53 , QuitRx 54 , STEPS 55 and Two2Quit 56 (Grant numbers and ClinicalTrials.gov registration numbers, where required, are provided in the acknowledgements). Participants were recruited from the Houston metropolitan area from a wide variety of sources including local print media, flyers, and collaborations with local healthcare institutions.…”
Section: Methodsmentioning
confidence: 99%